Christian interpretation of Esther before the Reformation - Biddle, Mark E. (Review and expositor, 2021)
This contribution to Review & Expositor’s issue on “Esther as Christian Scripture” surveys Esther scholarship before the Reformation with a view to identifying trends and with particular interest in the degree of any continuity that may bridge the Reformation as a point of demarcation. Contrary to what might be expected, this brief survey of the history of Christian Esther interpretation before the Reformation demonstrates that many of the issues confronting contemporary Esther scholarship surfaced in some form prior to the rise of modern critical scholarship (historicity, genre, gender relations, theological significance, etc.). A focus on the hebraica veritas after Jerome influenced Christian interpretation of the book down the path of allegory. Apparently pioneered by Aphrahat, Rhabanus Maurus gave the allegorical reading of Esther a form that became virtually standard in the half-millennium prior to the Reformation. In it, the allegorical significance of Ahasuerus (Jesus), Vashti (Jewry), Esther (the Church, Mary), and a number of details remained constant. The following two features of Esther interpretation surveyed here stand out negatively: the entire absence of concern for the book’s violence and the perverse but persistent interpretation of a book celebrating the deliverance of Jews in a supersessionist, even anti-Semitic, fashion.